2002
DOI: 10.1021/jo016371v
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Reactions in Crystalline Solids:  Predicting Photochemical Decarbonylation from Calculated Thermochemical Parameters

Abstract: A detailed thermochemical analysis of the alpha-cleavage and decarbonylation reactions of acetone and several ketodiesters was carried out with the B3LYP/6-31G* density functional method. The heats of formation of several ground-state ketones and radicals were calculated at 298 K to determine bond dissociation energies (BDE) and radical stabilization energies (RSE) as a function of substituents. Results show that the radical-stabilizing abilities of the ketone substituents play a very important role on the the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
37
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 26 publications
2
37
0
Order By: Relevance
“…Although the topochemical postulate suggests that preorganization in the crystal lattice controls the outcome of photochemical reactions in crystals, it is the intrinsic properties of the chromophore that ultimately determine the feasibility of a given photoreaction . We have previously suggested that Norrish Type I decarbonylation of crystalline ketones to give radical intermediates is a stepwise process contingent on: (1) α substituents that lower the bond dissociation energy of the two α‐bonds to be cleaved and (2) excited state reactivity occurring in the triplet manifold to slow down reversible bond formation long enough for the loss of CO to occur before the first acyl–alkyl radical pair returns back to the starting material . Recently, we extended the scope of reactivity with examples that involve singlet state photodecarbonylations in the crystalline solid state .…”
Section: Introductionmentioning
confidence: 99%
“…Although the topochemical postulate suggests that preorganization in the crystal lattice controls the outcome of photochemical reactions in crystals, it is the intrinsic properties of the chromophore that ultimately determine the feasibility of a given photoreaction . We have previously suggested that Norrish Type I decarbonylation of crystalline ketones to give radical intermediates is a stepwise process contingent on: (1) α substituents that lower the bond dissociation energy of the two α‐bonds to be cleaved and (2) excited state reactivity occurring in the triplet manifold to slow down reversible bond formation long enough for the loss of CO to occur before the first acyl–alkyl radical pair returns back to the starting material . Recently, we extended the scope of reactivity with examples that involve singlet state photodecarbonylations in the crystalline solid state .…”
Section: Introductionmentioning
confidence: 99%
“…This is essentially due to the “pre‐organization” of the reacting molecules in crystals and the inability of the reactant molecules to freely move in the crystalline state, in contrast to that in the gaseous and solution states. Wide‐ranging areas of interest in organic solid‐state chemistry include topochemical dimerization or polymerization that involves addition to CC double bonds,2 group‐transfer reactions in crystals,3 mechanistic organic photochemistry,4 generation of chiral products from achiral reactant molecules in crystalline solids,5 crystal‐to‐crystal reactions5c, 6 as tools for the development of green chemistry,7 reactions in co‐crystals8 and inclusion crystals,9 control of reactivity in the solid state by using linear molecular templates,10 reaction between co‐crystals,11 asymmetric synthesis in inclusion crystals by using chiral hosts,5c, 6a, 12 solid‐state reaction kinetics,13 prediction of reactivity by using computational methods,14 mechanochemical reactions3g and the development of functional materials 10c. The rationalization, prediction and control of structure and properties of organic solid phases is difficult due to the complex nature of weak intermolecular non‐covalent bonding 15.…”
Section: Introductionmentioning
confidence: 99%
“…While radical stabilizing groups are required to make the two bond cleavage reactions exothermic and as efficient as possible, triplet reactivity slows down the recombination of the primary acyl-alkyl radical pair (RP 1 ) so that the irreversible formation of the secondary radical pair (RP 2 ) by the rapid loss of CO may compete with bond formation back to the starting ketone (Scheme 1). 5 We have shown that this is a robust strategy that can be used in the synthesis of natural products with adjacent quaternary centers bearing psubstituents (Ph, alkenyl, carbonyl, cyano, etc.). 6 However, the need for radical-stabilizing groups and triplet reactivity limits the scope of the method.…”
mentioning
confidence: 99%
“…Given that there is a strong correlation between the bond dissociation energy (BDE) of s-bonds and their activation energies for a-cleavage, 5 we expect that a-cleavage should occur predominantly at the s-bond that produces the trityl-centered radical in RP 1 (Scheme 1). If this assumption is correct, the efficiency of product formation in the solid state will depend on the rate of decarbonylation from the acyl radical in RP 1 compared to the rate of bond formation back to the starting ketone.…”
mentioning
confidence: 99%